The Effect of Thinking Maps in The Achievement of Mathematics for The Fourth Scientific Grade Female Students And Their Beliefs Toward Mathematics - Salih Abdullah, Mudrika (Opción, 2019)
The present study aimed to identify the effect of teaching using thinking maps in the achievement of mathematics for the fourth scientific grade female students and their beliefs toward mathematics . The study sample consisted of (54) students distributed in two divisions, one of which was randomly selected to represent the experimental group that was taught using the thinking maps, while the other group represented the control group and were taught by the usual method. The design of the two equivalent groups with the post-test was used. The researcher prepared two tools, the first was test to measure the achievement consist of (25) paragraphs (13 objectivity items of multiple-choice type with four alternatives, and 12 subjectivity items) and the second tool were beliefs scale similar to the fifth Likert scale where it contains (30) items ,the since- rity and reliability of each tool has been verified. The results were treated using the t-test equation for two independent samples. The results showed that there was a statistically significant difference at (0.05) level of significance between the means performance of the experi- mental group and the control group in favor of the experimental group in each tool.